Role of national security of Council of Defense of Ukraine in the administrative adjusting of activity of public authorities in the fight against narcotic criminality - Калюжний, Ростислав Андрійович; Бобрицький, Леонід Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In the article are considered the problem questions of legal status and organizational role of constitutional organ - Council of national security and defence of Ukraine in the system of the administrative legal adjusting of activity of organs of executive power, which carry out the functions of fight against narcotic criminality.